2007
DOI: 10.1682/jrrd.2006.05.0057
|View full text |Cite
|
Sign up to set email alerts
|

Pain and combat injuries in soldiers returning from Operations Enduring Freedom and Iraqi Freedom: Implications for research and practice

Abstract: Abstract-Operation Enduring Freedom (OEF) and OperationIraqi Freedom (OIF) have resulted in a growing number of seriously injured soldiers who are evacuated to the United States for comprehensive medical care. Trauma-related pain is an almost universal problem among these war-injured soldiers, and several military and Department of Veterans Affairs initiatives have been implemented to enhance pain care across the continuum of medical services. This article describes several innovative approaches for improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(132 citation statements)
references
References 55 publications
1
131
0
Order By: Relevance
“…These mean scores are substantially better than those reported by multiple authors for early amputation [5,8,24]. Akula, et al reported the mean physical scores for early amputation were 16.2, and 15.6 for the psychological SIP [1].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…These mean scores are substantially better than those reported by multiple authors for early amputation [5,8,24]. Akula, et al reported the mean physical scores for early amputation were 16.2, and 15.6 for the psychological SIP [1].…”
Section: Discussionmentioning
confidence: 68%
“…One possible explanantion for these findings could involve chronic pain, a common sequelae of limb salvage and a major indication for conversion to amputation [6]. Both Clark, et al and Holbrook, et al reported that experiences involving war injuries in soldiers with poorly controlled pain resulted in chronic pain and posttraumatic stress disorder [8,19]. By removing the painful extremity patients may have reduced levels of chronic pain, resulting in both better functional and psychosocial scores following amputation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These multiple tours have often included high-intensity conflicts that result in higher rates of injury and trauma exposure. Pain is a significant clinical condition and PTSD is one of the most common psychiatric diagnoses among this population [7][8][9][10][11][12]. Although it is known that these are highly prevalent conditions among individuals returning from recent wars, an understanding of the complexity of the chronic pain and PTSD relationship is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Since spinal pain complaints are common in OIF/ OEF veterans [7][8], some of these patients are likely receiving care at VHA chiropractic clinics. However, no data have been published on chiropractic services for OIF/OEF veterans.…”
mentioning
confidence: 99%